Impact of Brand Advertising, Consumer Confidence, and Consumer Attitudes on Purchase of Honda Brand Vehicles in Banda Aceh City - Rizal, Syamsul; Yusuf, Zulfan (Indonesian Journal Economic Review (IJER), 2023)
The purpose of this study was to determine the impact of advertising, brand, consumer beliefs and consumer attitudes on purchasing Honda branded vehicles in Banda Aceh city. Advertisements, brands, consumer beliefs, and consumer attitudes are independent variables, and purchases are the dependent variables. This sample was conducted using an objective sampling method from 100 respondents using Honda brand vehicles, specifically vehicles produced up to 2019. The results showed moderate associations between advertising variables, brands, consumer beliefs, and consumer attitudes towards purchasing Honda vehicles in Banda Aceh City. Honda car purchases in Banda Aceh City are influenced by promotional variables, brands, consumer beliefs, and consumer attitudes, with the remaining 53.7% being influenced by other variables. Evidence for all independent variables in this study, partially using t-tests, shows that all independent variables in this study have a significant impact on Honda vehicle purchases in Banda Aceh City. On the other hand, the simultaneous validation using the F-test also showed that the variables advertising, brand, consumer beliefs, and consumer attitudes had a significant impact on the purchase of Honda brand vehicles in Banda Aceh city at the same time. Based on the results of multiple regression analysis, the hypotheses tested in this study are accepted.